Functional Properties of Protein Hydrolysates on Growth, Digestive Enzyme Activities, Protein Metabolism, and Intestinal Health of Larval Largemouth Bass (Micropterus salmoides) - Zhengyu Sheng; Giovanni M. Turchini; Jianming Xu; Zishuo Fang; Naisong Chen; Naisong Chen; Ruitao Xie; Haitao Zhang; Songlin Li (Frontiers in Immunology, 2022)
The present study was conducted to investigate the effects of dietary inclusion of protein hydrolysates on growth performance, digestive enzyme activities, protein metabolism, and intestinal health in larval largemouth bass (Micropterus salmoides). The experimental feeding trial presented in this study was based on five isonitrogenous and isolipidic diets formulated with graded inclusion levels of protein hydrolysates, and it showed that protein hydrolysates improved growth performance, reduced larval deformity rate, and increased the activity of digestive enzymes, including pepsin and trypsin. Gene expression results revealed that the supplementation of protein hydrolysates upregulated the expression of intestinal amino acid transporters LAT2 and peptide transporter 2 (PepT2), as well as the amino acid transporters LAT1 in muscle. Dietary provision of protein hydrolysates activated the target of rapamycin (TOR) pathway including the up-regulation of TOR and AKT1, and down-regulation of 4EBP1. Additionally, the expression of genes involved in the amino acids response (AAR) pathway, ATF4 and REDD1, were inhibited. Protein hydrolysates inhibited the transcription of some pro-inflammatory cytokines, including IL-8 and 5-LOX, but promoted the expression of anti-inflammatory cytokines TGF-β and IL-10. The 16S rRNA analysis, using V3-V4 region, indicated that dietary protein hydrolysates supplementation reduced the diversity of the intestine microbial community, increased the enrichment of Plesiomonas and reduced the enrichment of Staphylococcus at the genus level. In summary, protein hydrolysates have been shown to be an active and useful supplement to positively complement other protein sources in the diets for largemouth bass larvae, and this study provided novel insights on the beneficial roles and possible mechanisms of action of dietary protein hydrolysates in improving the overall performance of fish larvae.